Rancang Bangun Sistem Pentanahan Penangkal Petir Pada Tanah Basah dan Tanah Kering pada Laboratorium Teknik Konversi Energi - Herman Nawir; Muhammad Ruswandi Djalal; Sonong Sonong (Muhammadiyah University, Sidoarjo, 2018)
Lightning rods in the Laboratory of Energy and Protection Distribution System of Ujung Pandang State Polytechnic are not functioning properly so the resistance resistance tends to be large, this is not good for earthing. This problem can be overcome by remaking lightning rods on wet and dry soils. This activity was carried out to reduce the value of resistance resistance in connection with this, this activity was carried out by designing, assembling and collecting data carried out by testing, while data analysis was carried out by counting. Based on the results of the discussion concluded that the resistance resistance value obtained is smaller than the previous device. Evidenced by the results of the test where the resistance value on the rod electrode in dry conditions ranged from 1.56 to 2.40 Ohm while the previous tool ranged from 1.6 to 9.0 Ohm. Then for wet soil conditions that range from 0.45 to 1.29 Ohm, while the previous tool is around 1.8 - 5.25 Ohm